Concise Review: Process Development Considerations for Cell Therapy. (27th August 2015) - Campbell, Andrew; Brieva, Thomas; Raviv, Lior; Rowley, Jon; Niss, Knut; Brandwein, Harvey; Oh, Steve; Karnieli, Ohad
Abstract : This review presents an introduction to the process development challenges of cell therapies and describes some of the tools available to address production issues. A summary is provided of what should be considered to efficiently advance a cellular therapy from the research stage through clinical trials and finally toward commercialization. Abstract: : The development of robust and well-characterized methods of production of cell therapies has become increasingly important as therapies advance through clinical trials toward approval. A successful cell therapy will be a consistent, safe, and effective cell product, regardless of the cell type or application. Process development strategies can be developed to gain efficiency while maintaining or improving safety and quality profiles. This review presents an introduction to the process development challenges of cell therapies and describes some of the tools available to address production issues. This article will provide a summary of what should be considered to efficiently advance a cellular therapy from the research stage through clinical trials and finally toward commercialization. The identification of the basic questions that affect process development is summarized in the target product profile, and considerations for process optimization are discussed. The goal is to identify potential manufacturing concerns early in the process so they may be addressed effectively and thus increase the probability that a therapy will be successful. Significance: The present study contributes to the field of cell therapy by providing a resource for those transitioning a potential therapy from the research stage to clinical and commercial applications. It provides the necessary steps that, when followed, can result in successful therapies from both a clinical and commercial perspective.